A Novel Magnetic Integration High-Efficiency Converter with Low Ripple and High Dynamic Response for the Hybrid Power Supply Systems of All-Electric Aircraft - Li Chen; Haifeng Gao; Fengjie Shen; Yiyi Zhang; Liangjie Qiu; Lei Wang (Aerospace)
With the continuous improvement of battery energy density and converter power density, as well as the miniaturization and lightweighting of related airborne electrical equipment, all-electric aircraft with hybrid power supply systems provide more trade-off space and possibilities for the design of future aircraft. It is indispensable to search for a more valuable topology and apply it to airborne power supply. This paper proposes an airborne high-gain unidirectional DC-DC converter suitable for between low-voltage unit and high-voltage bus, which consists of interleaved magnetic integrated switched coupled inductor units and improved switch capacitor units. This paper first analyzes the steady-state operating characteristics under different modes; the new topology has higher voltage gain and lower stress. Secondly, in response to the challenges of high efficiency and high power density, we propose a magnetic integration design method and comprehensive experimental scheme based on the EIE-type magnetic core structure. This successfully integrates multiple discrete inductors into a single magnetic core. Furthermore, based on the comprehensive consideration of steady-state, transient performance and power density, the general design criteria for a high-gain switched coupled inductor are summarized through the equivalent mathematical model of reverse flux coupling. Additionally, by adjusting the coupling coefficient, the converter can achieve zero-voltage switching under light load conditions, demonstrating versatility and scalability and better meeting the application requirements of electric aircraft. The proposed prototype can provide voltage gain in the range of 12–22 times the input voltage gain by varying the input voltage from a 12–24 V fuel cell. The comprehensive performance of the converter, including steady-state, transient, and efficiency, was tested under D < 0.5 and D > 0.5. The experimental results show that the proposed converter possesses advantages such as high gain and low stress, a high dynamic response and low ripple, and high efficiency and high power density, which can provide a more advantageous DC-DC converter solution for airborne hybrid power supply systems.